Meningkatkan Self-Awareness Siswa SMP Melalui Bimbingan Konseling Islami Dengan Metode Client-Centered - Anisha Nurul Fatimah; Salma Emilia Azzahra (LPPM Politeknik Pratama, 2024)
Today's education does not only rely on students' abilities in cognitive intuition but also includes spiritual matters. The emotional stability that exists within students plays a major role in the formation of self-awareness, thereby giving rise to other intelligences in various aspects within the individual. Adolescence is a transition period from children to adults who have duties and demands for themselves and their environment. If teenagers are not able to carry them out, they will experience identity confusion and this will trigger actions or behavior that cannot support students' ability to have self-awareness and full awareness of oneself. Through Islamic counseling guidance, this research aims to provide theoretical benefits to increase students' self-awareness, especially in the scope of Islamic education. This research uses a qualitative descriptive method with observation and interview data collection techniques. From the research results, it was found that students' self-awareness can be increased by providing emotional support, and providing an open space that does not have the opportunity to judge, and guidance counselors who can listen also play a role in positioning themselves from the perspective of students who are undergoing counseling.